(untitled) (Stamford Journal of Microbiology, 2022)
This study was designed to evaluate the physicochemical and bacteriological qualities of well water situated close to graves. Total heterotrophic bacterial count (THBC), total coliform count (TCC) and fecal coliform count (FC) were done on nutrient agar, MacConkey and Eosine methylene blue agar, respectively, using spread plate method at incubation conditions of 37℃ for 24 hours for THBC and TCC whereas 44.5℃ for 24-48 hours for fecal coliforms. Membrane filtration was used for Vibrio spp. count on TCBS agar while conventional biochemical method was performed for bacterial identification. Isolated bacteria were subjected for antimicrobial resistant testing using 8 families of antibiotics. Bacteria with MAR index value of ≥75 were sent for genomic identification and sequencing. The average value of the ten water samples analyzed over the period of study had high total suspended solids (mg/l), phosphate (mg/l); magnesium ion (mg/l) contents and a very low dissolved oxygen mg/L content. The THB count was (5.0×107-1.35×108 CFU/ml), TCC count (3.55×105- 1.04×106 CFU/ml), FC count (2.10×105-6.90×105 CFU/ml) while Vibrio spp. count was 45-144 CFU/100 ml and the MPN estimated reading for coliform was also high. The percentage occurrence and MAR index value of the bacteria isolated from the well water, respectively were Vibrio spp. 23%; 75, Klebsiella spp. 20%; 100, Bacillus spp. 14%; 100, Staphylococcus spp. 14%; 62.5, E. coli 12%; 62.5, Pseudomonas spp. 12%; 75, Glycomyces spp. 3%; 100 and Proteus spp. 3%; 50. The closeness of the well to the grave makes the decomposing leachates with high organic, inorganic, biological and poisonous metals sink into the underground aquifers. Stamford Journal of Microbiology, Vol.12 (1) 2022: 47-53